LEADING ORGANIZATION MANAGEMENT INTO A FULLY GREEN SUPPLY CHAIN - Poonbua, Wutipark; Phasuk, Padcharee; อุทุมพร, นงเยาว์ (Academic Journal Phranakhon Rajabhat University, 2021)
Leading organizations aim to develop productivity and service efficiency to respond to customer needs worldwide by creating innovations in the business sector and trying to reduce unnecessary costs. However, recent global warming and PM 2.5 are huge problems that have been paid attention to by customers. In addition, some organizational activities impact the environment, such as energy consumption in production processes, using packaging materials that are difficult to degrade, and air pollution caused by transportation. Therefore, the organizations are unable to increase the operating revenue from neglecting the quality of life of their customers. One of the effective management frequently used by organizations is the sustainable development concept, which involves profit, customers, and the world. It considers what is gained rather than profit by focusing on promoting employees' quality of life, customers, and environmental protection to create happiness in work and value for society. The organizations will apply the principles of the green supply chain to businesses in terms of order management, production and quality control of goods, inventory management, warehouse management, transportation and distribution, and customer service with technology. Also, the organizations will build sustainable competitiveness in the market to respond to customer needs to attract new target groups who care about environmental products and services.